Relation of fovea palatine and vibrating line in different soft palatal forms - Chhetri, Shanti; Rathi, Ankita; Gupta, Neha (Journal of Nobel Medical College, 2019)
Background: The posterior palatal seal (PPS) area plays a major role in retention of a maxillary denture. Many dentures have failed due to faulty recording of posterior palatal seal area. Hence, locating posterior palatal seal area is a critical step in complete denture fabrication. Various techniques have been described in the literature for locating the posterior border of maxillary complete denture. One of the most commonly used methods is the one that uses anatomical landmark like fovea palatine for locating the palatal seal area. However, many studies show a wide range of variation regarding position of fovea palatine with the vibrating line. Materials and Methods: A total of 200 subjects were selected for the study and clinical examination carried out to mark the vibrating line and fovea palatine. The location of vibrating line whether it is anterior to fovea palatine, on the fovea palatine or posterior to the fovea palatine in the different soft palate type(Class I, II or III) was recorded using the phonation method. Results: The vibrating line was located interiorly to the fovea palatine in 70%, 54% and 60% of the subjects with Class I, II and III soft palate. The vibrating line was located on the fovea palatine in22%, 40% and 36% of the subjects with Class I, II and III soft palate and posteriorly to the fovea palatine in 23%, 5% and 3% of the subjects with Class I, II and III soft palate respectively. Conclusion: The vibrating line was predominantly found to be anterior to the fovea palatine in all the soft palatal forms.